The Effect of Urban Land Use Changing on Green Area Neighborhoods No. 336 & 338 in Baghdad – Case Study - Shireen Ihsan Khaza'al Hasson; Kadhim Faris Dhumad (Journal of Engineering, 2018)
The role of the green areas lies in being one of the systems that plays the vital role in achieving the environmental dimension besides the socio-cultural body and the economic dimension in the hidden value of ecosystem services. However, many developing countries are characterized by a state of low community environmental awareness, which coincides with the basic need for land for housing and other uses, to take precedence over nature protection strategies. In the absence of clear planning and long-term planning strategies, all this led to abuses and violations of urban land use. In Iraq, the situation became more apparent due to the political, security and social conditions that followed the year 2003. Hence, the research problem of the phenomenon of excesses on the use of green land in the Iraqi cities in general and Baghdad in particular, which led to many bad effects. The aim of the research is to explore the importance of green spaces and the value of biological diversity, and to detect the effects of the phenomenon of continuous abuses. In order to address the problem of research and achieve its objectives, the premise of its content has been developed: Green infrastructure as a hierarchical and interrelated thematic system that can contribute to the production of a basic design of the city that believes in its functions and enhances its role and ensure its sustainability. The study followed an analytical descriptive approach to data collection and vocabulary extraction in relation to green areas, levels and hierarchies, and the extraction of theoretical indicators for the effects of the changes that occurred on them. They were tested in practice in neighboorhoods no. 338, 336 in the city of Baghdad, in the light of a field analysis and survey. The research found a decline in the area of ​​green areas as their ratios do not meet the local and global standards required, especially with the increasing of urban and population density over the past decade. In addition to what the neighborhoods suffer from urban chaos and a severe shortage of infrastructure services. Greenness and its functional and visual role in beautifying the urban landscape can be observed only in the remaining agricultural use, in nurseries and orchards, which are private property that does not include the general population in the use of its functions.  Finally, the research presented its vision regarding the treatment of the negative effects that were diagnosed, in light of the strategy to provide green spaces in the random neighbourhoods at multiple levels, starting with the residential clusters, through the streets and roads pedestrians, and ended with the level of neighborhoods.